The characteristics of antibiotic resistance and phenotypes in 29 outer‐membrane protein mutant strains in Aeromonas hydrophila. (15th August 2019) - Li, Zeqi; Wang, Yuqian; Li, Xiaoyan; Lin, Zhenping; Lin, Yuexu; Srinivasan, Ramanathan; Lin, Xiangmin
Summary: Although many typical outer‐membrane proteins (OMPs) have been well characterized, the biological functions of many OMPs remain largely elusive. In this study, we successfully constructed 29 OMP knockout strains in the pathogen Aeromonas hydrophila, which account for about 50% of all predicted OMPs in this bacterial species. We then further validated the antibiotics' susceptibility characteristics against 20 antimicrobial reagents in these mutants considering several phenotypes. Our results showed that a total of 22 OMP mutants affected the susceptibility to at least one antibiotic. The deletion of some OMPs, such as ΔlamB and ΔbamA, revealed very important roles in the resistance to certain antibiotics. However, not a single OMP mutant presented a constant behaviour to all of the tested antibiotics, suggesting the existence of a complex intercellular regulation mechanism and a protein–protein interaction network underlying the OMP homeostasis in the presence of antibiotics. Meanwhile, some OMP mutants also affected biofilm formation, ECPase and haemolytic activity, and carbon resources utilization. This report demonstrates the biological functions of OMPs on a large scale and most of results have not been reported in A . hydrophila .